Cell and Molecular Biology Underpinning the Effects of PEDF on Cancers in General and Osteosarcoma in Particular - Chandolu, V.; Dass, Crispin (Hindawi Publishing Corporation, 2012)
Cancer is becoming an increasingly common disease in which abnormal cells aggressively grow, invade, and metastasize. In this paper, we review the biological functions of PEDF (pigmented epithelium-derived factor) against cancer, with a focus on a particular type of bone cancer called osteosarcoma. PEDF is a 50 kDa glycoprotein and is a potent inhibitor of angiogenesis, via its ability to decrease proliferation and migration of endothelial cells. This paper critically examines the anticancer activities of PEDF via its role in antiangiogenesis, apoptosis-mediated tumor suppression, and increased tumor cell differentiation. Recently, an orthotopic model of osteosarcoma was used to show that treatment with PEDF had the greatest impact on metastases, warranting an evaluation of PEDF efficacy in other types of cancers.